Six months of resveratrol supplementation has no measurable effect in type 2 diabetic patients. A randomized, double blind, placebo-controlled trial. (September 2016) - Bo, S.; Ponzo, V.; Ciccone, G.; Evangelista, A.; Saba, F.; Goitre, I.; Procopio, M.; Pagano, G.F.; Cassader, M.; Gambino, R.
Graphical abstract: Anti-inflammatory and metabolic effects of 6 months of resveratrol vs placebo in patients with type 2 diabetes mellitus. A double-blind randomized-controlled trial. Abstract: The polyphenol resveratrol is considered to exert many beneficial actions, such as antioxidant, anti-inflammatory, insulin-sensitizer and anticancer effects. Its benefits in patients with type 2 diabetes mellitus (T2DM) are controversial. Our aims were to determine whether resveratrol supplementation at two different dosages (500 and 40 mg/day) for 6 months i) reduced the concentrations of C-reactive-protein (CRP) and ii) ameliorated the metabolic pattern of T2DM patients. In the present double-blind, randomized, placebo-controlled trial, 192 T2DM patients were randomized to receive resveratrol 500 mg/day (Resv500 arm), resveratrol 40 mg/day (Resv40 arm) or placebo for 6-months. At baseline and at the trial end, CRP values, anthropometric, metabolic and liver parameters were determined. No serious adverse event occurred. A dose-dependent, though not significant, CRP decrease of 5.6% (Resv40 arm) and 15.9% (Resv500 arm) was observed vs placebo. We failed to detect significant differences in weight, BMI, waist circumference, and values of arterial blood pressure, fasting glucose, glycated hemoglobin, insulin, C-peptide, free fatty acids, liver transaminases, uric acid, adiponectin, interleukin-6, in both the Resv500 and Resv40 arms vs placebo. Total cholesterol and triglycerides slightly increased in the Resv500 arm. Subgroup analyses revealed that lower diabetes duration (in both Resv500 and Resv40 arms), and, in the Resv500 arm, younger age, aspirin use and being a smoker were associated with a significantly higher CRP reduction vs placebo. The supplementations with 40 mg/day or 500 mg/day resveratrol did neither reduce CRP concentrations, nor improve the metabolic pattern of T2DM patients.